Operating device logical operations on data in the masked representation - Коркішко, Л. М. (Problems of Informatization and Control, 2008)
The structures of devices operating logic operations on the data presented in masked . The list of logical operations are logical operations of multiplication and addition. The characteristics of complexity of these structures